2024
DOI: 10.3390/math12060907
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Platen Stiffness on a Specimen’s Failure Initiation Point and the Failure Pattern of Brittle Materials in the Standardized Uniaxial Compression Test

Diego-José Guerrero-Miguel,
Martina-Inmaculada Álvarez-Fernández,
Ramón Gutiérrez-Moizant
et al.

Abstract: Uniaxial compressive strength is a variable necessary for adequately characterizing a material’s mechanical properties. However, a specimen’s geometric deviations and elastic properties may lead to undesirable stress states, which cause strong discrepancies between the results of the uniaxial compression test and its theoretical foundations. While geometric deviations may cause non-uniform contact between the platen and the specimen, elastic properties can provoke severe end effects that disturb the local stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…In this sense, if all induced stress fields are independent of the tested material properties, provided that specimens are sufficiently long, no differences should be registered in the obtained failure patterns. In contrast to this assumption, many authors have suggested different failure patterns when testing conditions are altered [17,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, if all induced stress fields are independent of the tested material properties, provided that specimens are sufficiently long, no differences should be registered in the obtained failure patterns. In contrast to this assumption, many authors have suggested different failure patterns when testing conditions are altered [17,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is worth mentioning here that the purpose of this article is to address, from a scientific perspective, the influence of the relative stiffness between the press plates and the specimen (the ratio between their Young's modulus) on the different contact stress distributions. While according to best knowledge of the authors, no previous proposal regarding the use of press plates with different materials, depending on the tested specimen, can be found in the current literature, previous research proves that contact conditions influence the obtained failure pattern, the location of the failure initiation point, and hence, the registered material's compressive strength [25,26]. The results expressed in this article confirm that the influence of shearing stresses across the contact can be minimized, reaching neglectable levels for practical engineering purposes, by using platens, or intermediate thick cushions, with similar elastic properties to those of the tested specimen.…”
Section: Introductionmentioning
confidence: 99%